Market-Based Policy Instruments for Systemic Bank Restructuring - Bayoumi, Tamim (IMF Working Papers; Working Paper, 1998)
Since the early 1980s, well over 100 countries have experienced systemic bank insolvencies. An important innovation among the resulting policies for reestablishing bank soundness has been the reliance on market-based instruments and policies, in contrast to the largely non-market-oriented approach taken in the 1930s during the last big wave of banking crises. This paper surveys and assesses market-based policy instruments employed to overcome systemic bank problems. Considerations regarding the design and mix of instruments as well as cost-sharing arrangements are shown to be key aspects of effective bank restructuring. Selected country examples are used to illustrate best practices.